The Impact of Tertiary Study on the Labour Market Outcomes of Low-qualified School Leavers: An update - Sarah Tumen; Sylvia Dixon; Sarah Crichton (New Zealand Government, The Treasury, 2018)
This paper is an update of a previous study by Treasury (Tumen et al, 2015). It assesses the impacts of post-school education on the labour market outcomes of young people who leave school without the NCEA level 2 qualification. Specifically, it estimates the effects of low-level tertiary study on the employment rates, benefit receipt rates and earnings of young people who left school without completing NCEA level 2 and then enrolled at a tertiary institution while they were aged 15–21. The benefits of the further education are measured by comparing the students' post-study outcomes with those of matched comparison groups of other young people who also left school without NCEA level 2 but did not undertake any tertiary education. The current study differs from the previous one in that we allow the students in our study population a longer time period in which to start and complete their tertiary study and track their outcomes for a greater number of years after completion. The findings are similar to the findings of the previous study. Just over half (51%) of those who enrolled in a level 1–4 certificate programme had achieved a qualification by the time they were 22 years of age. Three years after finishing, the students who completed a qualification were 9.1 percentage points more likely to be employed and 4.8 percentage points less likely to be receiving a benefit than their matched comparisons. Five years after finishing, they were 9.2 percentage points more likely to be employed and 5.9 percentage points less likely to be on a benefit than their matched comparisons. While completion of a tertiary qualification was associated with positive employment impacts, we find no evidence of positive impacts on participants' level of earnings, after controlling for their employment status. In addition, the employment benefits of tertiary study were confined to the students who completed a qualification and were not experienced by the 49% who did not.
Keywords: I26; 330; Youth; foundation education; early school leavers; low qualifications; Junge Arbeitskräfte; Bildungsabschluss; Hochschule; Absolventen; Qualifikation; Arbeitsmarktintegration; Neuseeland